Two-electron CO2 Reduction Reaction Mechanism on Nickel Cobalt Phosphate Surface Doped by Transition Metal: A DFT Study - Primipara, Raka; Syaifullah, Dzaki Ahmad; Nuruzzahran, Muhammad Arkan; Wijayanti, Dyah Puspasari; AlMohamadi, Hamad; Mobarak, Nadhratun Naiim; Fathurrahman, Fadjar; Saputro, Adhitya Gandaryus (Directorate for Research and Community Services, Institut Teknologi Bandung, 2026)
In this study, we explore the activity and selectivity of the CO2 reduction reaction (CO2RR) to CO and HCOOH on pure and transition metal-doped NiCoPO(100) surfaces using density functional theory (DFT) calculations. The novelty of this work lies in demonstrating that substitutional doping with Mn, Fe, and Cu significantly alters the thermodynamic landscape of CO₂RR, particularly in enhancing selectivity toward HCOOH. While CO remains the dominant product on most surfaces, Mn-doped NiCoPO(100) uniquely reverses this trend by reducing the limiting potential for HCOOH formation to a value lower than that for CO production. Furthermore, Mn doping suppresses the competitive hydrogen evolution reaction (HER), steering the reaction pathway more selectively toward formic acid. These findings introduce Mn-doped NiCoPO as a promising and tunable catalyst platform for selective CO₂ to HCOOH conversion, providing valuable insights for designing efficient catalysts for sustainable carbon utilization.